Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Ponte, Rui M.; Carson, Mark; Cirano, Mauro; Domingues, Catia M.; Jevrejeva, Svetlana; Marcos, Marta; Mitchum, Gary; van de Wal, R. S. W.; Woodworth, Philip L.; Ablain, Michaël; Ardhuin, Fabrice; Ballu, Valérie; et al. (Frontiers in Marine Science, 2019)
A major challenge for managing impacts and implementing effective mitigation and adaptation strategies for coastal zones affected by future sea level (SL) rise is our very limited capacity to predict SL change on coastal scales, over various timescales. Predicting coastal SL requires the ability to monitor and simulate a multitude of physical processes affecting SL, from local effects of wind waves and river runoff to remote influences of the large-scale ocean circulation on the coast. Here we assess our current understanding of the causes of coastal SL variability on seasonal to multi-decadal timescales, including geodetic, oceanographic and atmospheric aspects of the problem, and review available observing systems informing on coastal SL. We also review the ability of current models and data assimilation systems to estimate coastal SL variations and of atmosphere-ocean global coupled models and related regional downscaling efforts to project future SL changes. We discuss (1) key observational gaps and uncertainties, and priorities for the development of an optimal and integrated coastal SL observing system, (2) strategies for advancing model capabilities in forecasting short-term processes and projecting long-term changes affecting coastal SL, and (3) possible future developments of sea level services enabling better connection of scientists and user communities and facilitating assessment and decision making for adaptation to future coastal SL change.